FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK PAJAK BUMI DAN BANGUNAN DI WILAYAH DKI JAKARTA - Fransisca Zagita; Aan Marlinah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine whether the socialization of taxpayers, service quality, awareness of taxpayers, knowledge of taxpayers, tax sanctions, and income levels on taxpayer compliance with land and building taxes in the DKI Jakarta area. This study uses taxpayers in the DKI Jakarta area as the object of research. There are 102 respondents who meet the criteria taken by distributing questionnaires in the DKI Jakarta area. The results of this study indicate that the socialization of taxpayers and taxpayer knowledge has a positive influence on taxpayer compliance. For service quality, taxpayer awareness, tax sanctions, and income level have no effect on taxpayer awareness.